Beyond the scalpel: Quality care and patient safety - Saqib Kamran Bakhshi; Shahryar Noordin; Saleem Islam; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2026)
Quality surgical care was traditionally viewed through the lens of definitive outcomes - low complication rates and better survival. These metrics, though fundamental, now epitomize only a fraction of what outlines high-quality surgical care. While technical skills and proficiency are important, the modern horizon of quality care in surgery encompasses patient safety, health systems, teamwork, communication and delivery of patient-centered, evidence-based care. This year’s theme of the Annual Surgical Conference, and this supplement - Beyond the Scalpel: Quality Care and Patient Safety – reflects this evolving landscape. In low- and middle-income countries, the quest for quality often unfolds against the backdrop of resource constraints, high patient volumes and a shortage of healthcare personnel.1 Providing quality care is the holistic responsibility of the healthcare system, not just clinicians. In addition to technical skills and practical knowledge, a conducive work environment enabling institutional policies, resource availability and organizational culture, strongly influence a surgeon’s performance. Patient safety is the cornerstone and top priority of healthcare institutions globally. It is more often compromised by system gaps and failures than by individual follies or knowledge constraints. Addressing these vulnerabilities is the first step towards meaningful improvement. Patient safety should be viewed as an essential component of ethical and effective care everywhere, and not a privilege for high-income settings. Continue..